Tipping points of ancient Japanese Jomon trade networks from social network analyses of obsidian artifacts - Sakahira, Fumihiro; Tsumura, Hiroomi (Frontiers in Physics, 2023)
The Jomon period of ancient Japan, characterized by hunting and gathering, lasted from 16,000 to 2,400 years cal BP. In this 13,000-year period, the geographical range of trade is known to have been extensive but may not have always been constant. We conducted obsidian social network analyses on a large dataset to explore the dynamics of trade networks and their tipping points during the Jomon period. This study clustered sites by geographical location and summarized obsidian artifacts in aggregate values by region to increase regional representativeness. This improved the readability and interpretability of the analysis results and decreased the distortion of results owing to a small sample of sites. The results showed that, for sites adjacent to one another, it is reasonable to group the total values by region and assess the regional representativeness of the findings. By framing the provenance and consumption areas as a bipartite graph and using network analyses among consumption areas, it was revealed that the obsidian trade network expanded throughout the Kanto region in the middle Jomon period (5,500–4,500 years cal BP) but regionalized in the late Jomon period (4,500–3,200 years cal BP). These periods were extracted as tipping points in the Jomon trade network. The timing of these tipping points possibly occurred during a period of major climate change. Therefore, these tipping points of obsidian trade networks may have been the result of population decline and migration caused by shifting coastlines and living infrastructure owing to climate change.